2012
DOI: 10.1155/2012/620962
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Chronic Periodontitis in HIV-Seropositive Subjects and the General Population in the Ga-Rankuwa Area, South Africa

Abstract: The effect of HIV infection on the prevalence and the rate of progression of chronic periodontitis is not clear. The aim of this study was to compare parameters associated with the severity of chronic periodontitis in terms of periodontal probing depths, gingival recession, plaque indexes, and bleeding indexes of HIV-seropositive subjects and healthy age-matched control subjects, and of HIV-seropositive subjects on highly active antiretroviral therapy and those not receiving such treatment. Two cohorts of subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…Conversely, another study demonstrated that lower levels of CD4+ were not associated with more periodontal disease, including HIV+ with or without HAART 39 . As remarked above, the increase in the frequency of BOP was not correlated to higher levels of CD4+, which is in agreement with the findings from other studies 33,34,40,41 . It should also be stressed that in the current analysis, when smokers and non‐smokers were examined together, no tested parameter correlated with viral load.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Conversely, another study demonstrated that lower levels of CD4+ were not associated with more periodontal disease, including HIV+ with or without HAART 39 . As remarked above, the increase in the frequency of BOP was not correlated to higher levels of CD4+, which is in agreement with the findings from other studies 33,34,40,41 . It should also be stressed that in the current analysis, when smokers and non‐smokers were examined together, no tested parameter correlated with viral load.…”
Section: Discussionsupporting
confidence: 90%
“…In conformity with this finding, Pavan et al 33 attributed the use of HAART to a low frequency of oral lesions in HIV+ patients. Moreover, measurements of PD in HIV+ without HAART might be higher compared with HIV+ patients using HAART with CP 34 . In addition, increased PD in HIV+ patients may be more frequent in patients without HAART 21 …”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies have shown no differences between HIV-infected and healthy subjects in caries severity, chronic periodontitis, or advanced periodontal diseases (14,15). Previously, we reported salivary microbial changes in HIV-infected patients (16).…”
mentioning
confidence: 80%
“…1,4,1013 Oral lesions are seen in HIV patients and can serve to determine the progress and the severity of the underlying disease. 14,15 Oral diseases, such as dental caries, periodontal disease, tooth loss, oral mucosal, and oropharyngeal cancers, HIV/AIDSrelated oral disease, and orodental trauma are major public health problems worldwide. 16 There is a need for careful oral examina tion as oral manifestations can act as an indicator for immune suppression, especially in resourcesdeficient clinical settings, and also in probable diagnosis of new cases of HIV.…”
Section: Introductionmentioning
confidence: 99%